Prayer - eternal dialogue with God in secularization, pandemic, and war conditions - Brînzea, Nicolae (Technium Social Sciences Journal, 2022)
In a world marked more and more by secularization, where man loses the character of a person in favor of that of an individual, in the difficult conditions brought to the fore by the pandemic and war, man tends to lose himself in the vicious circle of his own ego. In such conditions, in which man, although with many virtual friends, realizes that he is more alone than ever, prayer is the one that can provide him with the emotional and spiritual stability necessary nowadays, through the correct relationship with God, relationship through which man realizes that he is never alone.